2018
DOI: 10.1016/j.cep.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and application of ruthenium-doped SrTiO 3 perovskite catalysts for microwave-assisted methane dry reforming

Abstract: Synthesis, characterization, and application of ruthenium-doped SrTiO3 perovskite catalysts for microwave-assisted methane dry reforming

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 36 publications
(61 reference statements)
1
26
0
Order By: Relevance
“…Very recently, Gangurde and coworkers synthesized Ru-doped SrTiO 3 perovskite catalysts that could also absorb MW energy for DRM. 49 Nonetheless, an excessive amount of CO 2 was needed to be present in the feed gas to limit C formation. This, without doubt, increases the downstream burden to separate or recycle the unreacted CO 2 , leading to complexities in the DRM process.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Very recently, Gangurde and coworkers synthesized Ru-doped SrTiO 3 perovskite catalysts that could also absorb MW energy for DRM. 49 Nonetheless, an excessive amount of CO 2 was needed to be present in the feed gas to limit C formation. This, without doubt, increases the downstream burden to separate or recycle the unreacted CO 2 , leading to complexities in the DRM process.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…An enhancement of Ni particles' dispersion and stability may be provided via the deposition of noble metal nanoparticles. Noble metal particles, such as platinum, gold, rhodium, and ruthenium, may enhance the dispersion of nickel particles and inhibit carbon deposition [10,[12][13][14][15]. Arora et al [1] typed the properties of noble metals, such as a good dispersion ability in the form of nanoscale particles that promote the dissociative adsorption of hydrogen and oxygen, and the exposure of d-subshell electrons as the main features responsible for the high activity and coke resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Over the past decade, many attempts have been made to reform methane with CO2 under microwave irradiation. [24][25][26][27][28] Zhang et al reported MDR using microwave dielectric heating over an Al2O3 supported platinum catalyst. They claimed, due to the formation of hot spots under microwave irradiation, higher conversion and selectivity were obtained under microwave conditions than those obtained with conventional thermal process when operating at the same measured temperature.…”
Section: Introductionmentioning
confidence: 99%